Chapter 1: "Crime Fiction in German: Concepts, Developments and Trends" from book: Crime Fiction in German - Katharina Hall (European Crime Fictions, 2016)
This is a chapter from Crime Fiction in German: Der Krimi, edited by Katharina Hall. It is the first volume in English to offer a comprehensive overview of German-language crime narratives from the nineteenth century to the new millennium. It introduces readers to crime novels from Germany, Austria, Switzerland and the former East Germany, and examines under-researched areas such as Nazi crime fiction, Turkish-German crime fiction and the Afrika-Krimi.